RELATIONSHIP BETWEENWORK PLACE HEALTHAND SAFETYTRAINING AND EMPLOYEES’ COMMITMENTAT CADBURY NIGERIA LIMITED (Unilorin Journal of Lifelong Education, 2025)
This study was conducted to investigate the Relationship Between WorkplaceHealth and Safety (WHS) Training Programmeson Employees’ Commitment at Cadbury Nigeria Limited. The study enquired into the link between workplace health and safety trainingon safety climate and employees well-being. To achieve this purpose, two research questions and two hypotheses were raised and tested at 0.05 level of significance. The population of the study was all the employees of Cadbury Nigeria Plc.119 respondents were purposively selected for the sample size. A researcher-designed instrument,Health and Safety Training on Employees Commitment (WHSTEQ) Questionnaire was used to collect the data. The instrument was validated and tested for reliability using test – retest method .A reliability coefficient of 0.60 obtained was found to be statistically significant at p<0.05. Descriptive statistics (frequencies and percentages) were used for analyzing the research questions while PPMC was used to test the hypotheses. The study discovered that there is a significant relationship between WHS training and safety climate at Cadbury Nigeria Limited. The study also found there is a significant influence of WHS training on workers well-being at Cadbury Nigeria Limited. This study concluded that safe working places are profitable places whether measured in terms of the company’s market share, consumer reputation, or its ability to attract and retain workers, managers or investors. This study recommended that government should mandate every food and beverage organization to have an occupational health and safety department mandated to formulate the guidelines of health and safety programmes in their organisations.